Declining Trajectories of Co-occurring Psychopathology Symptoms in Attention-Deficit/Hyperactivity Disorder and Autism Spectrum Disorder: A 10-Year Longitudinal Study - Orm, Stian; Øie, Merete Glenne; Fossum, Ingrid Nesdal; Andersen, Per Normann; Skogli, Erik Winther (Frontiers in Psychiatry, 2021)
Objective: Our objective was to examine developmental trajectories of co-occurring psychopathology symptoms from childhood to young adulthood in individuals with Attention-Deficit/Hyperactivity Disorder (ADHD), individuals with Autism Spectrum Disorder (ASD), and typically developing (TD) individuals. Method: We assessed co-occurring psychopathology symptoms in 60 individuals with ADHD, 26 with ASD, and 40 TD individuals at baseline (T1; Mage = 11.72, 64% boys), two-year follow up (T2; Mage = 13.77), and 10-year follow up (T3; Mage = 21.35). We analyzed trajectories of internalizing behaviors, externalizing behaviors, and total problems with linear mixed models. Results: From T1 to T3, the ADHD group displayed a small decline in internalizing behaviors (d = -.49) and large declines in externalizing behaviors (d = -.78) and total problems (d = -.71). The ASD group displayed large declines in internalizing behaviors (d = -.79), externalizing behaviors (d = -.80), and total problems (d = -.89). From T1 to T2, the decline in externalizing behaviors and total problems were significantly smaller in the ADHD group compared with the ASD group. The ADHD and the ASD group displayed more co-occurring symptoms compared with the TD group at T3. Conclusion: Individuals with ADHD and ASD, respectively, displayed declines in co-occurring symptoms from childhood to young adulthood. Individuals with ASD displayed an earlier decline compared with individuals with ADHD. Compared with TD individuals, individuals with ADHD and ASD, respectively, continued to display elevated levels of co-occurring symptoms in young adulthood.